Perbedaan Keterampilan Toilet Training Sebelum Dan Sesudah Dilakukan Story Telling Pada Anak Prasekolah Di Tk Mardi Sunu Malang - Yulkarnain , Ineke; Maulidia, Rahmawati; Sari , Nining Loura (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Toilet training is an educational process to control urination and defecation correctly and regularly. One solution chosen to address the issue of toilet training skills is by using a storytelling model.Objective: To determine the difference in toilet training skills before and after storytelling is conducted on preschool children at TK Mardi Sunu Malang.Methods: This study used a pre-experimental design with a one-group pre-post test design and a cross-sectional approach. The sample in this study consisted of 36 respondents selected through a sampling technique.Results: The study showed that before storytelling, more than half of the children were in the fairly good category, totaling 31 respondents (86.1%), and after storytelling, there was improvement with the majority being 30 respondents (83.3%). The Wilcoxon test analysis resulted in a p-value of 0.000 (α ≤ 0.05).Conclusion: There is a difference in toilet training skills before and after storytelling among preschool children at TK Mardi Sunu Malang. Children can be taught and guided about toilet training from an early age. Future researchers can contribute by collaborating with health workers in toilet training screening.